PERSPECTIVES OF 3D TECHNOLOGIES IN PLANNING CONSTRUCTION INSTRUCTIONS (Conferencea, 2024)
The use of 3D technologies in the construction industry has significantly transformed traditional methods of project planning, design, and execution. This paper explores the current and future perspectives of 3D technologies in planning construction instructions, highlighting their benefits, challenges, and potential innovations. By providing enhanced visualization, precise simulations, and improved communication between stakeholders, 3D technologies are paving the way for more efficient and sustainable construction practices. This article also examines the impact of 3D printing, Building Information Modeling (BIM), and Virtual Reality (VR) in the construction process.